Predictors of Nonroutine Discharge Among Patients Undergoing Surgery for Grade I Spondylolisthesis: Insights From the Quality Outcomes Database (QOD). (1st September 2019) - Mummaneni, Praveen V; Bydon, Mohamad; Knightly, John; Alvi, Mohammed Ali; Goyal, Anshit; Chan, Andrew K; Guan, Jian; Biase, Michael; Strauss, Andrea; Glassman, Steven; Foley, Kevin; Slotkin, Jonathan R; et al.
Abstract: INTRODUCTION: Discharge to an in-patient rehabilitation facility or another acute care facility not only constitutes a postoperative challenge for patients and their care team but also contributes significantly to health-care costs. In the era of changing dynamics of healthcare payment models where the risk of cost over-runs are being increasingly shifted to surgeons and hospitals, it is important to understand better outcomes such as discharge disposition. In the current manuscript, we sought to develop a predictive model for factors associated with nonroutine discharge after surgery for grade I spondylolisthesis. METHODS: We queried the Quality Outcomes Database for patients with grade 1 lumbar degenerative spondylolisthesis undergoing a surgical intervention between July 2014 and June 2016. Only those patients enrolled in a multiside study investigating the impact of fusion on clinical and Patient Reported Outcomes (PROs) among patients with grade 1 spondylolisthesis were evaluated. Nonroutine discharge was defined as those that were discharged to postacute or nonacute care setting in the same hospital or transferred to another acute care facility. RESULTS: Of the 605 patients eligible for inclusion, 9.4% (n = 57) had a nonroutine discharge (8.7%, n = 53 discharged to an inpatient postacute or nonacute care in the same hospital and 0.7%, n = 4 transferred to another acute care facility). On multivariable logistic regression, after adjusting for an array of demographic, socioeconomic, clinical, and operative variables, factors found to be independently associated with higher odds of nonroutine discharge included higher age (OR 10.53, 95% CI 3.8-29.2, P < .001), higher BMI (OR 2.42, 95% CI 1.45-4.05, P < .001), depression (OR 4.97, 95% CI 2.10-11.77, P < .001), and length of stay (OR 3.4, 95% CI 2.3-4.9, P < .001). CONCLUSION: In this multisite study of a defined cohort of patients undergoing surgery for grade I spondylolisthesis, factors associated with higher odds of nonroutine discharge included higher age, higher BMI, presence of depression, and higher length of stay.